Structural Steel Detailing Practices--Good and Bad - Dobbie, Hugh (Engineering Journal, 2004)
This paper summarizes important concepts presented in the recent update of the AISC Detailing for Steel Construction manual. Specifically, the following topics are discussed: basic detailing conventions, project set-up and control, shop drawings and bills of material, detailing quality control and assurance, and electronic design and detailing. Recommended detailing practices are emphasized and contrasted with poor practices.